Research of the work productivity of STM32F407VGT6 with .Net MF - Shevchuk, Yu. V.; Protsenko, D. P.; Mikhieiev, A. I. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The losses of programmable platforms using STMF4DISCOVERY CPU — STM32F407VGT6 with using of .Net Micro Framework for the implementation of engineering and scientific algorithmic problems are studied in the paper. The impact baseline data number on the algorithms performance is estimated.